Simple Composting House for Production of Cassava Skin Compost and Cow Manure at Pendawa 1 Farmers Group in Candi Rejo Village - Sebayang, Nur Ulina Warnisyah; Akasah, Wida; Manurung, Vindy Rilani; Sinamo, Karina Nola (ABDIMAS TALENTA: Jurnal Pengabdian Kepada Masyarakat, 2023)
There are cassava farmers in Pendawa 1 Farmer Group located in Candi Rejo Village, Sibiru-biru District, Deli Serdang Regency. The resulting cassava is usually processed by women into Opak crackers (chips from flour with cassava). In the process of making Opak, it will produce cassava peel waste. The farmers have never treated the cassava peel waste, besides that cow dung waste is also left piled up near the cow cage. The main factor that underlies the farmer's not to carry out waste treatment because they do not have a place or area to process the waste. Thus, this problem must be addressed immediately so that the farmer group can carry out circular agriculture in agriculture and animal husbandry. The purpose of this activity is to form or develop a group of farmers who are economically and socially independent, help create peace and comfort in community life and improve the skills of members of the Pendawa 1 Farmer Group in managing waste into compost. The result of this activity is to build a simple composting house with a special design measuring 6m x 4m as an area to process waste into compost.